Clinical and safety outcomes of a prospective, eight-week and monocentric study of a multi-active topical serum in facial hyperpigmentation in Indian skin - Ketan Kulkarni; Anil Kukreja; Monika Chinda (International Journal of Research in Dermatology, 2026)
Background: Facial hyperpigmentation is a common dermatological concern in individuals with Fitzpatrick skin phototypes III-IV. Current treatment options are often limited by tolerability issues and restrictions on long-term hydroquinone use. This study evaluated the efficacy and safety of SOLGLO-AZ Serum, a hydroquinone-free multi-active topical formulation, in Indian adults with facial hyperpigmentation. Methods: In this prospective, open-label, monocentric study, 34 adults with facial hyperpigmentation were enrolled, of whom 32 completed the study. Participants applied SOLGLO-AZ serum once nightly for 8 weeks. Efficacy was assessed at baseline, day 30, and day 60 using clinical blemish scores and Antera 3D imaging-derived skin luminance (L*) and pigmentation indices. Safety and participant satisfaction were evaluated using clinical assessments and self-assessment questionnaires. Results: By day 60, mean blemish scores decreased by 25% (p<0.05), skin luminance (L*) increased by 18.8% (p<0.05), and mean pigmentation values decreased by 9.2% (p<0.05) compared with baseline. More than 93% of participants reported improvement in pigmentation, skin tone evenness, overall appearance, and satisfaction with the product. No clinically significant adverse events, erythema, edema, or irritation were observed. Conclusions: Once-nightly application of SOLGLO-AZ Serum for 8 weeks resulted in significant improvement in facial hyperpigmentation, high patient satisfaction, and excellent tolerability in Indian adults with Fitzpatrick skin phototypes III–IV. These findings support the use of hydroquinone-free multi-active topical formulations for the management of facial hyperpigmentation.